Analisis Peranan Literasi Teknologi dan Informasi Sebagai Variabel Moderating Dalam Hubungan Openness To Expereience, Conscientiousness, Agreeableness, Serta Neuroticism Dengan Perencanaan Karier Pada Generasi Z di Universitas Dharma Andalas - Lasti Yossi Hastini; Lucy Chairoel; Mellyna Eka Yan Fitri (Universitas Komputer Indonesia, 2021)
Career planning in Generation Z who are still in college and are preparing to face the world of work needs to be researched. Career planning can be viewed from a personality approach including Openness to Experience, Conscientiousness, Agreeableness, and Neuroticism. In addition, Career Planning can also be viewed from the ability of Generation Z to enter the world of work, one of which is Information Technology and Literacy. This study aims to provide empirical evidence regarding the role of Information and Technology Literacy as a moderating variable in the relationship of each of the four personality variables with Career Planning. This research was conducted on 243 active students of Dharma Andalas University and is a research with a correlational quantitative design. Data were analyzed by SPSS application. The results show that Information Technology and Literacy have different moderating roles for each relationship between Personality and Career Planning. Only the relationship between Neuroticism and Career Planning, Technology and Information Literacy does not act as a moderating variable. Key Words : Technology and Information Literacy; Moderating; Career Planning; Openness to Experience; Conscientiousness; Agreeableness; Neuroticism